Low-frequency normal mode in DNA HhaI methyltransferase and motions of residues involved in the base flipping - Luo, Jia (National Academy of Sciences, 2005)
The results of normal-mode analyses are in accord with the proposal that a low-frequency motion of the HhaI methyltransferase enzyme is responsible for base flipping in bound DNA. The vectors of the low-frequency normal mode of residues Ser-85 and Ile-86 point directly to the phosphate and ribose moieties of the DNA backbone near the target base in position to rotate the dihedral angles and flip the base out of the DNA duplex. The vector of residue Gln-237 on the major groove is in the proper orientation to assist base separation. Our results favor the major groove pathway and the protein active process in base flipping.